Stable isotope constraints on Holocene carbon cycle changes from an Antarctic ice core - Elsig, Joachim; Schmitt, Jochen; Leuenberger, Daiana; Schneider, Robert; Eyer, Marc; Leuenberger, Markus; Joos, Fortunat; Fischer, Hubertus; Stocker, Thomas F. (Nature (London), 2009)
Holocene carbon cycle A new atmospheric δ 13 C record derived from measurements of air trapped in the EPICA Dome C Antarctic ice core, combined with a simple carbon model, provides a high-resolution view of the carbon cycle during the Holocene, the current interglacial period that started about 11,000 years ago. Previous reconstructions had revealed significant changes in atmospheric CO 2 concentrations, but the processes responsible for these changes were unclear. The new data suggest that the 5 p.p.m.v. decrease in atmospheric CO 2 during the early Holocene resulted from an uptake of about 290 gigatons of carbon by the land biosphere together with carbon release from the ocean in response to carbonate compensation of the terrestrial uptake at the end of the last ice age. The 20 p.p.m.v. increase of atmospheric CO 2 during the later Holocene can be mostly explained in terms of carbonate compensation of earlier land biosphere uptake and coral reef formation, with a minor contribution from a small decrease of the land biosphere carbon inventory. Antarctic ice cores can be used to reconstruct atmospheric CO 2 concentrations, revealing significant changes during the Holocene epoch which started 11,000 years ago. Here, a highly resolved δ 13 C record is presented for the past 11,000 years from measurements on atmospheric CO 2 trapped in an Antarctic ice core. These data are combined with a simplified carbon cycle model to shed light on the processes responsible for the changes in CO 2 concentrations. Reconstructions of atmospheric CO 2 concentrations based on Antarctic ice cores 1 , 2 reveal significant changes during the Holocene epoch, but the processes responsible for these changes in CO 2 concentrations have not been unambiguously identified. Distinct characteristics in the carbon isotope signatures of the major carbon reservoirs (ocean, biosphere, sediments and atmosphere) constrain variations in the CO 2 fluxes between those reservoirs. Here we present a highly resolved atmospheric δ 13 C record for the past 11,000 years from measurements on atmospheric CO 2 trapped in an Antarctic ice core. From mass-balance inverse model calculations 3 , 4 performed with a simplified carbon cycle model, we show that the decrease in atmospheric CO 2 of about 5 parts per million by volume (p.p.m.v.). The increase in δ 13 C of about 0.25‰ during the early Holocene is most probably the result of a combination of carbon uptake of about 290 gigatonnes of carbon by the land biosphere and carbon release from the ocean in response to carbonate compensation of the terrestrial uptake during the termination of the last ice age. The 20 p.p.m.v. increase of atmospheric CO 2 and the small decrease in δ 13 C of about 0.05‰ during the later Holocene can mostly be explained by contributions from carbonate compensation of earlier land-biosphere uptake and coral reef formation, with only a minor contribution from a small decrease of the land-biosphere carbon inventory.